Evaluation of TGF-β1 and EGFR in Cleft Affected Lip Mucosa - Rimdenoka, Olga; Pilmane, Māra (Acta medica Lituanica, 2021)
Background. The morphopathogenesis of orofacial cleft development is only partly understood; therefore, it is important to identify factors, which possibly could be involved in it. The aim of the study was to evaluate the distribution of TGF-β1 and EGFR-containing cells in cleft affected lip mucosa.Materials and Methods. The study group included lip mucosa tissue samples from 14 patients with orofacial cleft. The control group contained 11 healthy oral mucosa tissue samples. The tissue sections were stained by immunohistochemistry for TGF-β1 and EGFR. The expression of positive structures was graded semiquantitatively. IBM SPSS 26.0 was used for statistical analysis, Spearman`s rank correlation and Mann-Whitney U tests were performed.Results. Mostly few to moderate number (+/++) of TGF-β1-containing cells was found in epithelium, also the same number of fibroblasts and macrophages was seen in the lamina propria of cleft affected lip mucosa. Meanwhile, healthy oral mucosa on average demonstrated a moderate number (++) of TGF-β1-containing epithelial cells, fibroblasts, and macrophages. A variable, mostly indistinct number of EGFR-containing cells was seen in the epithelium of cleft affected lip mucosa, meanwhile, mostly no (0) EGFR positive cells were found in the epithelium of healthy mucosa. Statistically significantly less TGF-β1-containing cells were found in the epithelium of cleft affected lip mucosa than in the healthy mucosa (U=33.000; p=0.015). Also, the lamina propria of cleft affected lip mucosa showed statistically significantly less TGF-β1 immunoreactive fibroblasts and macrophages than the healthy mucosa (U=28.500; p=0.006).Conclusions. The decreased number of TGF-β1-containing epithelial cells, fibroblasts and macrophages in cleft affected lip mucosa proves the role of problematic tissue remodelation in the cleft pathogenesis. The distribution of EGFR in cleft affected and healthy mucosa is similar and possibly does not play a role in the cleft development of humans.
Keywords: orofacial cleft; lip mucosa; TGF-β1; EGFR